Development of community empowerment based on zonation in the Gunung Halimun Salak National Park, Indonesia - Pitra Panderi; Dolly Priatna; Sata Yoshida Srie Rahayu (Universitas Pakuan, 2022)
Local communities surrounding Gunung Halimun Salak National Park are highly dependent on the national park area. Economic development is crucial to improving the livelihood of the local communities around the park area. Additionally, to ensure that the preservation of the national park will be supported by the surrounding communities, activities within the local communities can also align with the management of the national park. In Indonesia, national parks are managed through a zonation system, in which potential areas that satisfy the biophysical conditions will be considered for development activities that support the local communities. We analyze the biophysical condition of the area, zonation of area, and socio-economic conditions of communities to identify the types of potential community development activities. We conducted a survey of biophysical conditions, as well as interviews and focus group discussions with relevant stakeholders. The results of the study reveal five types of community development activities with the most potential, namely 1) development of tourism; 2) conservation partnership schemes; 3) cooperation on ecosystem restoration; 4) development of forest plant cultivation to provide seeds for economic benefits; 5) utilization of ecosystem services, such as water and hydroelectric power plants.